2006
DOI: 10.1038/sj.onc.1209426
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of ATR to sites of ionising radiation-induced DNA damage requires ATM and components of the MRN protein complex

Abstract: ATM and ATR are two related kinases essential for signalling DNA damage. Although ATM is thought to be the principle kinase responsible for signalling ionising radiation (IR)-induced DNA damage, ATR also contributes to signalling this form of genotoxic stress. However, the molecular basis of differential ATM and ATR activation in response to IR remains unclear. Here, we report that ATR is recruited to sites of IR-induced DNA damage significantly later than activation of ATM. We show that ATR is recruited to IR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
132
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(142 citation statements)
references
References 63 publications
8
132
0
2
Order By: Relevance
“…Although the localization and activation of ATR at DSB sites has been detected in cyclin A-positive cells in S-and G 2 -phase cells (Jazayeri et al, 2006), there is also evidence indicating that ATR might be activated before the onset of DNA synthesis (Adams et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the localization and activation of ATR at DSB sites has been detected in cyclin A-positive cells in S-and G 2 -phase cells (Jazayeri et al, 2006), there is also evidence indicating that ATR might be activated before the onset of DNA synthesis (Adams et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in yeast (Cha and Kleckner, 2002) and Xenopus (Shechter et al, 2004) model systems have shown that ATR homologs function at active replicons to suppress DNA breaks and prevent fork stalling. Recent reports have demonstrated that ATR is activated at double-strand DNA break (DSB) sites, suggesting that ATR contributes to IR responses in human cells (Adams et al, 2006;Cuadrado et al, 2006;Jazayeri et al, 2006;Myers and Cortez, 2006). These reports have shown that ATR colocalizes with phosphorylated Chk1 at sites of DSBs (Adams et al, 2006;Jazayeri et al, 2006) and that Chk1 phosphorylation after IR exposure is largely ATRdependent.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting ssDNA coated by RPA, then initiates ATR signalling (Jazayeri et al, 2006). Studies by Cuadrado et al, Yoo et al, and Adams et al, have provided further experimental evidence to support ATM dependent activation of ATR is required in double strand break DNA repair (Cuadrado et al, 2006;Yoo et al, 2007;Adams et al, 2006). Importantly, ATR has also been shown to activate ATM in response to the presence of ssDNA damage (Stiff et al, 2006).…”
Section: Atr Activation In Response To Single Strand Dna Damagementioning
confidence: 93%
“…Additional evidence in support of this was reported by Zhang et al (2005) who showed that the MRN complex is required for ATR-dependent phosphorylation of SMC1; for cell survival; the intra-S-phase checkpoint and genomic stability after exposure to UV. Furthermore, recruitment of ATR to sites of radiation-induced DNA damage and activation requires ATM and components of the MRN complex (Adams et al, 2006;Myers and Cortez, 2006).…”
Section: Viral Infection and In Vitro Models To Investigate The Role mentioning
confidence: 99%